Penerapan Strategi Komunikasi Lembaga Dakwah Kampus Sebagai Sarana Aktivis Dakwah di IAIN Langsa - Sembiring, Masdalifah; Gandhi, Al Mutia; Nurhaliza, Siti; Fikri, Soleh (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2024)
When it comes to preach (da'wah), it can be challenging to connect with university students as the main target audience, particularly those who are not very involved in religious activities. Additionally, there are limitations in terms of human resources, budget, and infrastructure that can impact the implementation of effective communication tactics. This study aims to analyze the communication strategies utilized by campus da'wah institutions as a means of assistance for da'wah activists at IAIN Langsa. The data was obtained through in-depth interviews with da'wah institution managers and activists, as well as participatory observation of da'wah activities. The results show that effective communication strategies play a vital role in extending the reach of da'wah, reinforcing the Islamic identity of students, and boosting participation in da'wah activities. The importance of improving communication strategies to boost the impact of da'wah on campus and promoting a deeper understanding of the role of da'wah institutions in molding a community based on Islamic values at IAIN Langsa is highlighted by this research.